ANALISIS PENGARUH PENGUMUMAN LAPORAN KEUANGAN TERHADAP RETURN SAHAM - Cahyani, Linda; Simanjuntak, Aaron M. A.; Hutadjulu, Linda (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study purpose are to prove a December 31 financial statements have information content in the presence of abnormal stock returns are significant and fundamental variables to test the effect of abnormal stock returns. The data used in this research is secondary data obtained from the Indonesia Stock Exchange. The research sample as many as 114 companies go public on the Stock Exchange, where the method used is purposive sampling is a sampling method by setting criteria for certain criteria. With this method of pooling of data (2012-2013) the number of samples (n) = 228. The data were analyzed using the t test and the F test in hypothesis testing. The first hypothesis testing results showed that there was no difference in abnormal stock returns before and after the announcement of the financial statements. While the test results influence fundamental variables partially (t test) between the variable accounts receivable, inventory, gross profit, earnings per share (EPS), operating cash flow (OCF), return on assets (ROA) and one control variable sized companies against abnormal return shares are all variables did not affect the abnormal stock return. This is supported by test results determination coefficient is 0.036, which means 3.6% value of cumulative abnormal return (CAR) which can be explained by the independent variable and the remaining 96.4% is explained by other variables outside the model.